Epistemological conception of the role of the media in education (2018)
The media represent, together with education, one of the forces of change of the universal society. The recent years have imposed modalities and technologies that raise their influence, instantaneity and geographic penetration or reach, to turn them into fundamental axis. That media power is conceived, although it is not a current reality for now, as a valuable tool to strengthen the educational process, through the production of news, reports, interviews, spaces, documentaries and programs that reinforce teaching originated in the classroom; that revalue the importance and validity of the training process; and strengthen the values of both nationality and individual personality; and taking into account that ninety percent of Venezuelan households have television sets and eighty four percent of radio receivers. The two areas are detailed in their origin and as processes, to make their importance sit down. The particular media situation is analyzed in the Municipality of Zea, Mérida State, where there are two radio stations and one television station, in addition to primary, secondary and higher schools. Teachers with management positions, media directors and producers are the key informants. It is located within the qualitative paradigm and the ethnographic method. The information was analyzed by means of triangulation and interpretation based on the design of Bahamonde and carried out in two moments, the first with the double entry Alpha Matrix that gave the synthesis of the relevant social phenomenon, expressed in graphic one. The second, with the Beta Matrix generating the theoretical Projection expressed in Graph two. All with the aim of generating the epistemological conception of the role of the media embodied in the conclusions and contributions of the research.